Exploring Students' Responses to Constructivist Learning Elements Across Learning Styles and Topic Preferences - Habi Septiawan; Ag. Bambang Setiyadi; Muhammad Sukirlan; Khairun Nisa; Flora Flora (Yayasan Darusssalam Bengkulu, 2026)
This study explores students’ responses to constructivist learning elements across different learning styles and topic preferences in an English as a Foreign Language (EFL) context. Specifically, it examines how students with different learning styles and preferred topics perceive five constructivist learning elements: Complex Learning Environment/Authentic Task, Social Negotiation, Multiple Perspectives, Knowledge Construction, and Student Ownership. Thirty-five students participated in the study and were grouped into eight categories based on the combination of three learning styles (auditory, visual, and kinesthetic) and three topic preferences (Entertainment & Pop Culture, Experience & Story, and Personal & Daily Life). Data were collected through a questionnaire adapted from constructivist learning theory and analyzed descriptively using mean scores. The findings revealed variations in students’ responses across learning styles and topic preferences. The Kinesthetic–Entertainment & Pop Culture group demonstrated the highest overall mean score (M = 3.65), while the Auditory–Personal & Daily Life group obtained the lowest (M = 2.73). Across all groups, Complex Learning Environment/Authentic Task consistently received the lowest ratings, indicating that students were less positive toward complex and authentic learning tasks than other constructivist elements. In contrast, Student Ownership emerged as the highest-rated element in most groups. Additionally, students who shared the Entertainment & Pop Culture preference, regardless of learning style, reported the highest scores on Multiple Perspectives. These findings suggest that topic preferences may play an important role in shaping specific constructivist learning experiences, while learning styles influence the overall level of student responses.